Response of South Asia PM2.5 pollution to ammonia emission changes and associated impacts on human health - Yuanlin Wang; Eiko Nemitz; Samuel J. Tomlinson; Edward J. Carnell; Liquan Yao; Janice Scheffler; Tomas Liska; Clare Pearson; Ulrike Dragosits; Chandra Venkataraman; Srinidhi Balasubramanian; Rachel Beck; et al. (Environment International)
Countries in South Asia are suffering severe PM2.5 pollution with rapid economic development, impacting human health and the environment. Whilst much attention has been given to understanding the contribution of primary emissions, the contribution of agriculture to PM2.5 concentrations, especially from agricultural ammonia (NH3) emissions, remains less explored. Using an advanced regional atmospheric chemistry and transport modelling system (WRF-EMEP) with a new estimate of anthropogenic NH3 emissions inputs, we estimate the influence of agricultural NH3 emissions on surface PM2.5 in South Asia and evaluate the health impacts and the economic losses attributable to PM2.5 in 2018. Results show that WRF-EMEP can reproduce magnitudes and variations of PM2.5 well, with a high annual mean PM2.5 concentration that exceeds 120 µg/m2 and mainly appeared in the Indo-Gangetic Plain. We estimate 2,228,000 (95 % Confidence Interval: 2,052,000–2,400,000) premature deaths and US$ 596,000 (95 % CI: 549,000–642,000) million in economic losses are attributable to total ambient PM2.5 under the current emissions. We calculate that NH3 emissions are associated with 11 % of the annual average PM2.5 concentrations across South Asia. Changes in PM2.5 concentrations follow a non-linear response to NH3 emissions reductions, highlighting increased efficiency with 70 %–100 % reductions in NH3 emissions reductions. We estimate that 247,000 (227,000–265,000) premature deaths and US$ 66,000 (61,000–71,000) million economic losses through this pathway can be attributed to NH3 emissions. These findings confirm that in the current NH3-rich chemical environment of South Asia, the efficiency of PM2.5 reduction is only moderately sensitive to the reduction in intensity of NH3 emissions until emissions are cut very severely. Thus, SO2, NOx and NH3 emissions controls need to be considered jointly for greater mitigation of ambient secondary PM2.5 in South Asia.